Winning the Merger Endgame: - Deans, Graeme K. (McGraw-Hill, 2003)
Thirteen years ago, the experts at A. T. Kearney embarked on a landmark, worldwide study of business mergers. Encompassing 25,000 companies across 24 industries in 53 countries, the study revealed much crucial information that was previously unknown about business consolidation. This book shares those revelations and insights with senior executives, consultants, and industry analysts involved in the merger process. More important, it builds on those findings to present readers with a solid game plan for winning the consolidation game. Readers learn about the consolidation cycles through which industries pass, how to identify where in the cycle their industry currently lies, how to leverage that knowledge in determining which organizational changes they need to make and when they need to make them, and how to develop and deploy the most successful merger strategies